The use of a virtual patient to follow changes in arterial blood gases associated with therapeutic thoracentesis. Issue 11 (November 2018) - Stecka, Anna M; Gólczewski, Tomasz; Grabczak, Elżbieta M; Zieliński, Krzysztof; Michnikowski, Marcin; Zielińska-Krawczyk, Monika; Korczyński, Piotr; Krenke, Rafał
Purposes: Some controversies exist on the effect of therapeutic thoracentesis (TT) on arterial blood oxygen tension. The aim of this study was to evaluate this issue using a previously developed virtual patient. Methods: The analysis was based and supported by clinical data collected during 36 TT. Pleural pressure and transcutaneous oxygen and carbon dioxide pressures (PtcO2 and PtcCO2 ) were measured during pleural fluid withdrawal. Arterial blood oxygen tension and arterial CO2 tension (PaO2 and PaCO2 ) were analysed in simulations that mimicked TT. Minute ventilation was adjusted to maintain arterial CO2 tension at a constant level unless arterial blood oxygen tension fell below 8 kPa. Specifically, the influence of hypoxic pulmonary vasoconstriction efficiency was tested. Results: In patients, PtcCO2 remained at an approximately constant level (average amplitude: 0.63 ± 0.29 kPa), while some fluctuations of PtcO2 were observed (amplitude: (1.65 ± 1.18 kPa) were observed. In 42% of patients, TT was associated with decrease in PtcCO2 . Simulations showed the following: (a) there were similar PaO2 fluctuations in the virtual patient; (b) the lower the hypoxic pulmonary vasoconstriction efficiency, the more pronounced the PaO2 fall during fluid withdrawal; and (c) the lower the atelectatic lung areas recruitment rate, the slower the PaO2 normalization. The decrease in PaO2 was caused by an increase of pulmonary shunt. Conclusion: Therapeutic thoracentesis may cause both an increase and a decrease in PaO2 during the procedure. Pleural pressure decrease, caused by pleural fluid withdrawal, improves the perfusion of atelectatic lung areas. If the rate of recruitment of these areas is low, a lack of ventilation causes the arterial blood oxygen tension to fall. Effective hypoxic pulmonary vasoconstriction may protect against the pulmonary shunt.